Native lamin A/C proteomes and novel partners from heart and skeletal muscle in a mouse chronic inflammation model of human frailty - Elzamzami, Fatima D.; Samal, Arushi; Arun, Adith S.; Dharmaraj, Tejas; Prasad, Neeti R.; Rendon-Jonguitud, Alex; DeVine, Lauren; Walston, Jeremy D.; Cole, Robert N.; Wilson, Katherine L. (Frontiers in Cell and Developmental Biology, 2023)
Clinical frailty affects ~10% of people over age 65 and is studied in a chronically inflamed (Interleukin-10 knockout; 'IL10-KO') mouse model. Frailty phenotypes overlap the spectrum of diseases ('laminopathies) caused by mutations in LMNA. LMNA encodes nuclear intermediate filament proteins lamin A and lamin C ('lamin A/C'), important for tissue-specific signaling, metabolism and chromatin regulation. We hypothesized that wildtype lamin A/C associations with tissue-specific partners are perturbed by chronic inflammation, potentially contributing to dysfunction in frailty. To test this idea we immunoprecipitated native lamin A/C and associated proteins from skeletal muscle, hearts and brains of old (21-22 month) IL10-KO versus control C57Bl/6 female mice, and labeled with Tandem Mass Tags for identification and quantitation by mass spectrometry. We identified 502 candidate lamin-binding proteins from skeletal muscle, and 340 from heart, with 62 proteins identified in both tissues. Candidates included frailty phenotype-relevant proteins Perm1 and Fam210a, and nuclear membrane protein Tmem38a, required for muscle-specific genome organization. These and most other candidates were unaffected by IL10-KO, but still important as potential lamin A/C-binding proteins in native heart or muscle. A subset of candidates (21 in skeletal muscle, 30 in heart) showed significantly different lamin A/C-association in an IL10-KO tissue (p<0.05), including AldoA and Gins3 affected in heart, and Lmcd1 and Fabp4 affected in skeletal muscle. To screen for binding, eleven candidates plus prelamin A and emerin controls were arrayed as synthetic 20-mer peptides (7-residue stagger) and incubated with recombinant purified lamin A 'tail' residues 385-646 under relatively stringent conditions. We detected strong lamin A binding to peptides solvent exposed in Lmcd1, AldoA, Perm1 and Tmem38a, and plausible binding to Csrp3 (muscle LIM protein). These results validated both proteomes as sources for native lamin A/C-binding proteins in heart and muscle, identified four candidate genes for Emery-Dreifuss muscular dystrophy (CSRP3, LMCD1, ALDOA, PERM1), support a lamin A-interactive molecular role for Tmem38A, and supported the hypothesis that lamin A/C interactions with at least two partners (AldoA in heart, transcription factor Lmcd1 in muscle) are altered in the IL10-KO model of frailty.